Kinetic Monte Carlo Simulation of Metallic Nanoislands Grown by Physical Vapor Deposition (Communications in Computational Physics, 2011)
We report kinetic Monte-Karlo (KMC) simulation of self-assembled synthesisof nanocrystals by physical vapor deposition (PVD), which is one of the most flexible,efficient, and clean techniques to fabricate nanopatterns. In particular, self-assembledarrays of nanocrystals can be synthesized by PVD. However size, shape and densityof self-assembled nanocrystals are highly sensitive to the process conditions such asduration of deposition, temperature, substrate material, etc. To efficiently synthesizenanocrystalline arrays by PVD, the process control factors should be understood in detail.KMC simulations of film deposition are an important tool for understanding themechanisms of film deposition. In this paper, we report a KMC modeling that explicitlyrepresents PVD synthesis of self-assembled nanocrystals. We study how varyingcritical process parameters such as deposition rate, duration, temperature, and substratetype affect the lateral 2D morphologies of self-assembled metallic islands onsubstrates, and compare our results with experimentally observed surface morphologiesgenerated by PVD. Our simulations align well with experimental results reportedin the literature.